Role of subcutaneous vacuum suction drain in prevention of abdominal wound complication in emergency laparotomy - Pandey, Vinod Kumar; Chandra, Dhruv; Kumar, Raj; Singh, Anil; Pratap, Tej; Agarwal, Shubham; Yadav, Ashish (International Surgery Journal, 2020)
Background: Some of the most common wound complications following laparotomy include hematoma formation, seroma formation, wound infection, burst abdomen and wound dehiscence. Closed-suction drains (CSDs) help to drain any wound collection and also reduce any dead space in the wound thereby promoting healing and preventing complication. Methods: We conducted a prospective study and included patients presenting with acute abdomen in emergency department. Patients were selected as per inclusion and exclusion criteria. Two groups (group A and B) with equal number of patients were created based on closed envelope technique. CSD was placed in the wound of patients in group A. Wound healing and complications were compared between the two groups. Results: 50 patients were included in the study with 25 in each group. Hematoma formation was found to be significantly more among group B (24.0%) compared to group A (4.0%). Seroma formation (p value =0.03917), SSI rate (p value =0.039) and wound dehiscence/burst abdomen (p value =0.0415) was more in group B than group A. The mean wound healing time (days) and mean hospital stay (days) was significantly more in group B. Conclusions: Placing a subcutaneous vacuum suction drain at the time of abdominal wall closure during emergency laparotomy results in better wound healing and reduces postoperative wound complication, hospital stay time, morbidity and also decreases overall healthcare cost.